DERMATOGLIFOS EN lJNA POBLACION COLOMBIANA - Vargas Quintero, María Victoria; Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
A group oj minetithree colombian people were studied taking the prints oj their hands (Types ojpictures onjingers and the area between them, palm trirradii and places where the principle lines end). The characterization ojthe poption shown a high percentage oj ulnar loop on the jingers (68.9 per 100), jollowed by whorlas (23.2 per 100), radialloops (5.6 per 100) and arches (4 per 100). Themost jrecuentpictures in the interdigital are as was the open camp (73.4 per 100) and, distal loop (20.2 per 100). The trirradii t' was the most jrecuent oj the palmar trirradii (54.3 per 100). On both hands the average more jrecuent on transversality was 13 (34. 4 per 100 ), also on the modall3etha type (45. 7 per 100) the TRCjor men was 134 andjor women 108. 7.    1 Profesor, Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana Apartado Aéreo 56710 Bogotá, Colombia2. Profesor, Departamento de Biología Facultad de Ciencias, Universidad Nacional de Colombia Bogotá.